Analysing the national notifiable diseases surveillance system in South Africa - Benson, Frew Gerald (My University, 2018)
Background Outbreaks of infectious diseases contribute to premature mortality and underscore the importance of effective disease surveillance and response systems. There is limited knowledge on the performance of the South African notifiable disease surveillance system (NDSS). Objective The aim of this PhD study was to analyse the NDSS of South Africa. The specific objectives were to: analyse key informants’ perspectives on system attributes of the National NDSS; analyse the NDSS attributes through comparing notifications with laboratory surveillance; determine the factors influencing provider compliance with the NDSS; and make policy recommendations to improve the effectiveness of the NDSS. Methods This thesis combined a novel comparative analysis of laboratory and notification records for three tracer conditions of measles, meningococcal meningitis, and typhoid with two cross-sectional, analytical studies among NDSS key stakeholders (n=169) and health care providers (n=1050) respectively. STATA® 14 was used to conduct quantitative, statistical analyses. Results The key stakeholders’ survey had an 84% response rate: 25% perceived the system to be acceptable; 51%, flexible; 45%, timely; 61%, useful; and 74%, simple. Stakeholders with more experience were less likely to perceive the NDSS as acceptable (OR 0.91, 95 % CI: 0.84–1.00, p = 0.041); those in disease detection were less likely to perceive it as timely (OR 0.10, 95 % CI: 0.01–0.96, p = 0.046) and those participating in National Outbreak Response Team were less likely to perceive it as useful (OR 0.38, 95 % CI: 0.16–0.93, p = 0.034). vii For all three diseases, fewer cases were notified than laboratory confirmed. Completeness for the laboratory system was higher for measles (63% vs. 47%, p<0.001) and meningococcal meningitis (63% vs. 57%, p<0.001), but not for typhoid (60% vs. 63%, p=0.082). Stability was higher for the laboratory (all 100%) compared to notified measles (24%, p<0.001), meningococcal meningitis (74%, p<0.001), and typhoid (36%, p<0.001). Representativeness was also higher for the laboratory (all 100%) than for notified measles (67%, p=0.058), meningococcal meningitis (56%, p=0.023), and typhoid (44%, p=0.009). The sensitivity of the NDSS was 50%, 98%, and 93%, and the PPV was 20%, 57%, and 81% for measles, meningococcal meningitis, and typhoid, respectively. The response rate for the health care provider (HCP) survey was 90%. In the year preceding the survey, 58% diagnosed a notifiable disease; 92% of these HCPs reported the disease, but only 51% notified correctly to the Department of Health. Factors influencing notification were HCPs perceptions of workload (OR 0.84, 95% CI 0.70 - 0.99, p=0.043) and that notification data are not useful (OR 0.84, 95% CI 0.71 - 0.99, p=0.040). Conclusion The NDSS in South Africa performed poorly on most of the system attributes. In addition, HCP compliance with the NDSS was suboptimal. The study generated new knowledge on the performance of the NDSS in South Africa, which should inform the revitalisation and reforms of the system.
A thesis completed by published work Submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, June 2018
Keywords: Communicable Diseases; Infection; Bacterial Infections